2014
DOI: 10.3928/19404921-20130918-01
|View full text |Cite
|
Sign up to set email alerts
|

Key Neuropsychiatric Symptoms in Common Dementias: Prevalence and Implications for Caregivers, Clinicians, and Health Systems

Abstract: The purpose of this study was to compare neuropsychiatric symptoms (NPS) among people with common dementias and equip interdisciplinary clinicians and health services planners with large-sample data necessary to plan care for patients and families. We analyzed selected variables from baseline assessments of older adults with dementia of one or more etiologies (N = 3,768) from the National Alzheimer's Coordinating Center data repository. Dementias included Alzheimer's disease (AD), Lewy body dementia (DLB), beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 45 publications
(50 reference statements)
1
30
0
1
Order By: Relevance
“…Results of the NPI indicate that anxiety, which has a lower prevalence in other forms of dementia [36,37,38], was observed in 55.3%, suggesting that this could be added to the diagnostic criteria. Interestingly, an earlier research found that anxiety was a risk factor for DLB [39].…”
Section: Discussionmentioning
confidence: 99%
“…Results of the NPI indicate that anxiety, which has a lower prevalence in other forms of dementia [36,37,38], was observed in 55.3%, suggesting that this could be added to the diagnostic criteria. Interestingly, an earlier research found that anxiety was a risk factor for DLB [39].…”
Section: Discussionmentioning
confidence: 99%
“…Agitation, which is commonly observed in people with dementia (PWD) in nursing homes [1,2,3,4,5], may have many negative impacts on the PWD [6,7,8], their caregivers [9,10,11], and society [12]. Acupressure is a therapy that originates from traditional Chinese medicine (TCM).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of NPI score between the VaD patients and normal control group has been described in other studies [12]; this study focuses on the evaluation of the NPI in patients with vascular dementia. As shown in (Table 2), the NPI scores of the delusions, hallucinations, agitation, depression or dysthymia, apathy, irritability, abnormal behavior, appetite and eating disorders in the VaD group were significantly higher than those in normal control group (P<0.05).…”
Section: The Results Of Npi Assessmentmentioning
confidence: 97%
“…The correlations of frequency of emergence of NPI [12] mental behavior symptoms in VaD patients were analysed. As shown in Table 4, the results showed that there was significant correlation between delusions and hallucinations (r=0.753, P=0.001), depression and anxiety (r=0.596, P=0.001), agitation and irritability (r=0.591, P=0.002), which suggested that some obvious related sub-symptoms might form sub syndrome, namely the delusions and hallucinations (psychosis), depression/anxiety and dysthymia (affective disorder), agitation and irritability (loss of control behavior).…”
Section: Correlation Analysis Among Npi Itemsmentioning
confidence: 99%